Izbrisani med politiko zanikanja in eksemplaričnostjo romana - Juvan, Marko (Primerjalna književnost, 2016)
The exemplarity of novels by Miha Mazzini, Polona Glavan, and Dino Bauk touched on the Slovenian discourse of "organized innocence" (Jalušič) and, within the limits of aesthetic representation, attempts to arouse sympathy for people removed from the Slovenian population register (the "erased"). These novels metonymically represent the population that Slovenian post-independence biopolitics robbed of rights and reduced to "bare life" (Agamben): that is, the exemplary narratives focus on a humanized victim of the removal, while depicting the relations of so-called ordinary people to this large-scale violation of human rights.
Keywords: Mazzini, Miha, 1961-; Glavan, Polona, 1974-; Bauk, Dino, 1973-; literatura in družba; Slovene literature; slovenska književnost; človekove pravice; human rights; izbrisani; The Erased; etnonacionalizemn; Trauma; travma; zanikanje krivde